Analysis of Administrative Supervision on the Return of Immigration Documents for Children with Multiple Citizens Who Choose Foreign Citizens - Afrisyab Zacki Martendi; Nadine Melisa Lumban Tobing; Reza Astro Haryono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The emergence of Government Regulation Number 2 of 2007 concerning Procedures for Acquiring, Losing, Canceling, and Regaining Indonesian Citizenship as well as the issuance of Government Regulation Number 31 of 2013 concerning Implementing Regulations of Law Number 6 of 2011 concerning Immigration requires children with dual citizenship who choose citizenship Foreigners are required to return all documents that can provide identical proof of Indonesian Citizens including Immigration Documents such as Passport of the Republic of Indonesia and Affidavit. However, in its implementation in the field, there are still many subjects with dual nationality who choose foreigners and those in charge not to do this. This of course can cause other problems. There should be awareness and strict sanctions should be made on those who do not carry out these obligations. Thus, if the issuance of legal rules governing the sanctions is expected to provide a deterrent effect for those who do not carry out these obligations. The existence of this journal writing is expected to be useful for various parties while for the Immigration ranks so that it can be used as reference material in conducting further research.